Pre-literacy Skills Case of a Rural School in Uttar Pradesh - Shukla, Ruchi (JOURNAL OF INDIAN EDUCATION, 2016)
Rural India has a large number of first-generation learners. The Socio-economic Status (SeS) combined with the absence of a proper schooling environment in homes i.e., no exposure to printed material, communication opportunity and community ignorance to such factors result in low or no pre-literacy/readiness skills. Pre-literacy skills are understood in terms of a child’s vocabulary, phonological sensitivity, print knowledge, knowledge of the alphabet and an understanding of common print concepts like print goes from left to right and from top to bottom on a page. Pre-literacy skills or readiness for formal schooling has been proven by research to be an important contributor to literacy, school success and education, at large. The government through ‘Aanganwadis’ has taken adequate steps to nurture this pre-requisite, especially for the firstgeneration learners. The ground realities, however, suggest otherwise.